Effectiveness of an intervention to manage occupational stress among bus drivers of Sri Lanka Transport Board in Colombo District, Sri Lanka - Dhananja Illangasinghe; M. A. A. P. Alagiyawanna; D. B. D. L. Samaranayake; Neil Fernando (College of Community Physicians of Sri Lanka, 2023)
Introduction: Occupational stress among bus drivers is on the rise in the world. Mental health promotion programs can be effective in managing job stress in occupational groups. Objectives: To assess the effectiveness of a multi-component intervention to manage occupational stress among bus drivers of Sri Lanka Transport Board of Colombo District. Methods: A cluster randomized control trial was performed to assess the effectiveness of the intervention. Drivers were selected by randomization from all 12 depots in Colombo District. The intervention was carried out in six depots and controlled in the other six depots. Both arms consisted of 72 drivers. The mental health promotion-stress management intervention package was delivered for six months. Outcomes were assessed based on pre- and post-test stress levels. Process indicators were also determined to assess the effectiveness of the intervention. Results: All the participants were males. Response rate in the intervention group was 97.2%. Pre-intervention prevalence of occupational stress in the intervention group was 50% (n=36) and it was 58.33% (n=42) in the control group. This difference was not statistically significant (p=0.316). The post-intervention occupational stress level in the intervention group was 40.28% (n=29) and in the control group was 56.94% (n=41). This difference was statistically significant (p=0.045). In the intervention group, twelve drivers with occupational stress shifted to normal stress levels after the intervention, while five drivers who had normal stress levels, developed occupational stress afterwards (6.94%). This difference within the intervention group was not statistically significant (OR=2.4; 95% CI: 0.845, 6.81; p=0.145). Level of satisfaction on the overall programme was stated as excellent by 86% of the drivers in the intervention group. Conclusions & Recommendations: Stress management intervention was effective in reducing occupational stress among drivers. Mental health promotion programs need to be conducted on the recruitment of bus drivers.